Characteristic Features of Terms in English Football TV Commentaries - Lukáš, Zdeněk (Univerzita Pardubice, 2011)
The thesis deals with terminology and formulaic language in English football TV commentaries. The aim is to investigate characteristic features of terms and multi-word items, especially the form, word classes, and syntactical function, which appear in the language of football commentaries. In the theoretical part, linguistic literature relevant to the topic is analysed in order to create a concept of criteria which is later employed as a framework in the practical part of the paper. The practical part focuses on the analysis of collected football commentary corpus. The terms and multi-word items are identified and qualitatively scrutinised for their characteristic features. Subsequently, the occurrence of the individual forms of terminological units is quantitatively processed. Finally, the author offers his interpretations of the findings.
Charakteristické rysy termínů v anglických fotbalových TV komentářích
Keywords: jazyk fotbalových komentářů; fotbalová terminologie; termíny; kolokace; sousloví; idiomy; fráze; klišé; frázové sloveso; jazyk lexikálních formulí; language of football commentaries; football terminology; terms; collocation; compound; idiom; phrase; cliché; phrasal verb; formulaic language